Metode Topsis Sistem Pendukung Keputusan Penentuan Siswa/Siswi Berprestasi di SMP XX - Irnawati Irnawati; Julizal Julizal (Jurnal Publikasi Manajemen Informatika, 2024)
The TOPSIS method in the Decision Support System for Determining Outstanding Students at SMP XX explains that this method is used to select alternatives (students) who have the closest distance to the positive ideal solution and the furthest from the negative ideal solution. This method considers criteria such as academic grades, activeness in extracurricular activities, and disciplinary attitudes. By implementing TOPSIS, it is hoped that objective and accurate decisions can be made in determining outstanding students. The TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method was chosen because of its reliability in overcoming complexity and uncertainty in multi-criteria decision making. Eka got a preference value of 0.31144246, Elsa got a preference value of 0.62095919, Frits got a preference value of 0.80287008, and Ninik got a preference value of 0.38000306. With the results of these preference values, it can be determined that Frits gets rank 1, Elsa gets rank 2, Ninik gets rank 3, and Eka gets rank 4.